2021
DOI: 10.3390/nu13061802
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Deficiencies and Stunting Were Associated with Socioeconomic Status in Indonesian Children Aged 6–59 Months

Abstract: Micronutrient deficiencies and stunting are known as a significant problem in most developing countries, including Indonesia. The objective of this study was to analyze the association between micronutrient deficiencies and stunting with socioeconomic status (SES) among Indonesian children aged 6–59 months. This cross-sectional study was part of the South East Asian Nutrition Surveys (SEANUTS). A total of 1008 Indonesian children were included in the study. Anemia, iron deficiency, vitamin A deficiency, vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
15
0
4
Order By: Relevance
“…A previous study found that taking Vitamin A supplements is related to a considerable increase in adolescent development [7]. Vitamin A supplementation, according to this study, may help to avoid stunting.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A previous study found that taking Vitamin A supplements is related to a considerable increase in adolescent development [7]. Vitamin A supplementation, according to this study, may help to avoid stunting.…”
Section: Discussionsupporting
confidence: 62%
“…Stunting can be influenced by a lack of Vitamin A in the diet [5]. Then, Vitamin A is involved in a variety of physiological activities in the body, including eyesight, cell differentiation, acquaintance, growth and development, reproduction, cancer and heart disease prevention, and hunger suppression [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that the differences in iron status between males and females arise after adolescence 7 , 8 . Some studies have reported substantial sex differences in serum ferritin levels in infants and pre-pubertal children 9 11 . Serum ferritin levels differ significantly according to sex, suggesting a sex-dependent relationship for ferritin and neurodevelopmental function risk.…”
Section: Introductionmentioning
confidence: 99%
“…We also found 14 articles from citations and hand searching, which resulted in an additional manuscript (15) . Notable exclusions include one study which did not specify the vitamin D cut-off value (34) , one study that included Dutch residents of Indonesian ethnicity (35) , two studies (36,37) that were generated from the same dataset (38) , one poster presentation (39) that were ultimately published as a full A c c e p t e d A r t i c l e paper (40) , and five studies (41)(42)(43)(44)(45) were also excluded as they were part of Southeast Asian Nutrition Surveys (SEANUTS) study (15) . Therefore, seven studies (15,38,40,(46)(47)(48)(49) are available for systematic review and meta-analysis (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%